Effects of crystalline orientation, twin boundary and stacking fault on the crack-tip behavior of a mode I crack in nanocrystalline titanium. (December 2019) - Cai, Jun; Mi, Changwen; Deng, Qiong; Zheng, Chenyi
Highlights: A combined modeling and theoretical study was performed for a Mode I crack in Ti. Effects of crystalline orientation, twin boundary and stacking fault were explored. Depending on nanostructures, either brittle or ductile crack behavior is possible. Elevating loading rate helps promote the brittle-to-ductile propagation transition. Simulations and theoretical predictions result in consistent crack-tip behaviors. Abstract: In this work, molecular dynamics simulation and linear elastic fracture mechanics were employed to analyze the crack-tip behavior of a Mode I crack in nanocrystalline titanium. The effects of crystalline orientation, twin boundary and stacking fault on crack propagation were taken into account. Simulation results demonstrate that the crack-tip behavior and thus the crack propagation mode strongly depend on crystalline orientations and plane defects. Cracks lying on the hexagonal close-packed basal plane, the prismatic plane, or along a stacking fault plane defect propagate in a brittle manner, without involving proper dislocation emissions and twin nucleations in the crack-tip vicinity. In contrast, cracks show a ductile propagation behavior when aligned along the pyramidal plane, the 10 1 ¯ 2 plane, or the 10 1 ¯ 2 〈 1 ¯ 011 〉 twin boundary. For these cases, local crack-tip plasticity and crack-tip reconstructions are found to play significant roles. The impact of strain rate on the crack-tip behavior of a basal crack was also investigated in detail. Five strain rates varied between 10 9 s − 1 and 10 10 s − 1 were considered. With increased strain rates, a brittle-to-ductile transition was clearly observed for crack propagation. The desired transition can be attributed to the high stress and energy concentrations near the crack-tip under elevated strain rates, leading to the successive emission and propagation of partial dislocations. To verify and validate the simulation results, a theoretical analysis on the competition between brittle and ductile crack propagations was also implemented. The theoretical predictions based on the linear elastic fracture mechanics were found to reasonably agree with the simulation results. The observations and conclusions deduced from the combined modeling and theoretical study are helpful to the better understanding of fracture mechanics in nanocrystalline titanium.